Koli fisherman repairing nets in a large workshop - Mumbai Archive Project Team (Jio Institute, 2024)
Koli fishermen know how to repair nets, and modest-sized nets can be repaired with the help of family members. However, major damage requires a specialized repair facility. These repairs are done by professionals who employ teams of men working together in large workshops.